Medical-Grade Honey Enhances the Healing of Caesarean Section Wounds and Is Similarly Effective to Antibiotics Combined with Povidone-Iodine in the Prevention of Infections-A Prospective Cohort Study - Amadou Bocoum; Senna J. J. M. van Riel; Soumana Oumar Traoré; Elisabeth Florine Ngo Oum II; Youssouf Traoré; Augustin Tioukani Thera; Seydou Fané; Bakary Tientigui Dembele; Niels A. J. Cremers (MDPI AG, 2023)
Caesarean sections (CS) are becoming increasingly popular. The antibiotic resistance crisis and relentless risk of infections, especially in developing countries, demand alternative treatment options. Medical-grade honey (MGH) exerts antimicrobial and healing properties. This study aims to evaluate the effect of MGH treatment on CS wound healing and postoperative complications when compared to conventional treatment (antibiotics in combination with povidone-iodine). In this prospective cohort study, 766 CS patients were included and evenly divided into two groups. The treatment group (n = 383) received an MGH-based formulation (L-Mesitran Soft) and the control group (n = 383) received antibiotics (Amoxicillin) combined with povidone-iodine. The wound healing time and complication rate were determined for both groups, and subsequently, predisposing factors for complications among the baseline characteristics and non-patient-related parameters were determined. The baseline characteristics were similar for both study groups, supporting a homogenous distribution. Postoperative complications were experienced by 19.3% of the patients in the control group and 18.8% in the treatment (MGH) group. The treatment group experienced significantly more superficial pus discharge than the control group, while the latter experienced significantly more deeper pus discharge. BMI, age, duration of hospitalization, anesthesia, and duration of CS could affect the complication risk. MGH significantly enhanced wound healing until day 42. On average, the healing time with MGH was 19.12 ± 7.760 days versus 24.54 ± 8.168 days in the control group. MGH is a potent alternative treatment to antibiotics and povidone-iodine because while the complication risk is similar, MGH has additional benefits. MGH promotes wound healing and does not bear the risk of resistance.